La capacidad explicativa de la personalidad oscura sobre el rasgo de inteligencia emocional - Bonfá-Araujo, Bruno (2022)
This study aimed to identify the capacity of the dark personality to explain the emotional intelligence trait. The sample comprised 395 subjects, aged 18 to 30 years (M = 21.19; SD = 1.75), who responded to the Short Dark Triad, Short Sadistic Impulse Scale, Spitefulness Scale and Emotional Skills Inventory. To achieve the proposed objective, a path analysis model was performed. The results indicated that sadism, achiavellianism and narcissism positively explain the dimensions of emotional intelligence, while psychopathy and pitefulness explain it negatively. The findings of this study highlight caution when interventions are carried out to increase emotional intelligence in individuals with dark traits, since they can use it for emotional manipulation.